Tahfizh Al-Qur'an Ma'had Al Jami'ah Alumni Program Git in Al-Qur'an Literature in the City of Samarinda - Siti Romlah; Muhammad Fajri (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
Ma'had Al Jami'ah UINSI Samarinda has established the Tahfizh Al-Qur'an Program since 2015, so it should already have alumni, so it is necessary to do research related to the impact of establishing the program through the activities of its alumni. Therefore, this study aims to identify and analyze the progress of alumni in the city of Samarinda, the progress of alumni in Al-Qur'an literacy and public perceptions of the work of alumni of the Tahfizh Al-Qur'an Ma'had Al Jami'ah Program. The type of research used to achieve the objectives of this research is field research with a descriptive qualitative approach, data collection techniques through observation, documentation and interviews, informants in this study were thirteen alumni and seven stakeholders. The data were analyzed using interactive data techniques which had stages of data collection, data condensation and conclusion drawing, and data triangulation was also carried out to test the validity of the data. Finally, this research shows that there are 14 alumni who take part in Samarinda City, thirteen of them take part in Al-Qur'an literacy and have given a sense of satisfaction to users.